HUBUNGAN PERILAKU KEPEMIMPINAN, KOMPETENSI KERJA PEGAWAI DAN EFEKTIVITAS BIROKRASI (Suatu Studi di Sekretariat Daerah Kabupaten Bolaang Mongondow Utara) - LAIYA, DEWI LANTI; Posumah, Johnny Hanny; Tulusan, Femmy (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : This study is based on the assumption of the importance of leadership behavior and employee competence in realizing the effectiveness of the organization or bureaucracy. By taking research location in the Regional Secretariat Bolaang North Mongondow, this study wanted to answer the questions: (1) the extent to which the relationship of leadership behavior with the effectiveness of the bureaucracy? and the extent to which the relationship of employee competence to the effectiveness of the bureaucracy?This study used a survey method. Subjects were civil servants in the Secretariat of the North Mongondow Bolaang area, with respondents as many as 48 people taken at random from the 72 civil servants. The main instruments used in data collection was a questionnaire / questionnaire and assisted with interview techniques. The data analysis using descriptive statistical analysis of frequency distribution / percentage, chi-square and contingency coefficient. The result showed: (1) the value of chi-square and contingency coefficient of correlation between the behavior of the leadership of the effectiveness of the bureaucracy are significant at the 99% confidence level. (2) the value of chi-square and contingency coefficient of correlation between the effectiveness of employee competence of the bureaucracy was also significant at 99% confidence level.Based on the results of the data analysis conclusion: (1) leadership behavior has a strong positive correlation and significant to the effectiveness of the bureaucracy. (2) competency employee has a close positive correlation and significant to the effectiveness of the bureaucracy. Contrary to the conclusion of the study results suggested that the quality of leadership behavior and employee competence would beenhanced to achieve maximum effectiveness of the bureaucracy.Keywords: leadership behavior, job competence, the effectiveness of the bureaucracy.